Associations between state scope of practice laws and US physician assistant wages from 1997 to 2017: a longitudinal analysis - Shahpar Najmabadi; Trenton J Honda; Virginia L Valentin (BMJ Open)
Objective The purpose of this study is to determine whether, and to what degree, variations in physician assistant (PA) state scope of practice (SOP) laws across states are associated with (1) PA median wage over time and (2) if a specific SOP key element has greater impact on PA median wage than others. We hypothesise that expanded SOP laws will be associated with higher PA wage.Design Longitudinal analysis from 1997 to 2017.Setting Fifty states and the District of Columbia (US capital region).Participants Employed PAs from 1997 to 2017.Methods Four national data sets were combined to allow for longitudinal analysis of state-level annual PA wage and state SOP laws. We used linear regression models to explore the associations of SOP elements with PA wage in 5-year intervals and individual growth models to assess the change in PA annual wage over the study period.Results There was a 220% increase in weighted PA annual wage over two decades. There was a positive linear correlation between annual wage and age in 2012 and 2017 (r=0.52, p<0.01; r=0.29, p=0.04, respectively). The adjusted R2 for individual SOP elements in the selected years were all small (range: 0.0–0.29), with no appreciable pattern across time for any SOP element. In 1997, several SOP laws show association with median wage but this impact disappears over time.Conclusions PA median wage has risen over twofold in the past two decades, with the rise in PA wage mainly explained by time and provider age. In 1997 some SOP elements were associated with increased average wage; however, the impact of this increase diminished over time in all such instances. As the PA profession moves towards Optimal Team Practice, future research should examine if this move towards greater autonomy impacts wage.